APOBEC3A expression in penile squamous cell carcinoma - Heller, Martina; Prigge, Elena-Sophie; Kaczorowski, Adam; Knebel Doeberitz, Magnus von; Hohenfellner, Markus; Duensing, Stefan (Pathobiology, 2017)
Background: APOBECs (apolipoprotein B mRNA-editing catalytic polypeptides) are cytidine deaminases that have been implicated in the host defense against viruses by blocking viral replication. They have also been shown to play a role in genome hypermutation in several human cancers. An APOBEC3 hypermutation signature has been discovered in cervical cancer, which is intimately associated with infection by high-risk human papillomaviruses (HPVs). At the same time, HPV genomes themselves are subject to DNA editing by APOBECs. Similar to cervical cancer, a proportion of penile squamous cell carcinomas (SCCs) is etiologically driven by high-risk HPVs, but very little is known about the role of APOBECs in penile SCC development and progression. Methods: A series of 34 penile SCCs was analyzed for the expression of APOBEC3A protein by immunohistochemistry. HPV genotyping was carried out using a bead-based multiplex hybridization assay preceded by BSGP5+6+ primer-based amplification. Results: We found a frequent reduction of APOBEC3A protein expression in the invasive parts of the majority of HPV-negative penile SCCs. In contrast, the majority of HPV-positive penile SCCs retained APOBEC3A expression during malignant progression. Conclusion: Our results suggest that APOBEC3A expression is downregulated during progression towards invasiveness in HPV-negative penile SCC, but maintained in HPV-positive penile SCC. How high-risk HPV-infected tumor cells tolerate high APOBEC3A, which appears to exert tumor suppressive functions in HPV-negative penile SCCs, remains to be elucidated.
Gesehen am 23.04.2018